(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
This is a case considered to be a suicide by the police as it was depicted to be a case of partial hanging. During autopsy examination multiple injury marks were observed on the neck and fracture of hyoid bone. As the above mentioned findings are usually not seen in case of suicidal hanging, these unusual post-mortem findings lead the investigation from different medico legal angles by forensic expert. An attempt has been made in this case to correlate the presence of injuries on the dead body in relation to partial hanging.